Oleander Stem and Root Standardized Extracts Mitigate Acute Hyperglycaemia by Limiting Systemic Oxidative Stress Response in Diabetic Mice - Priyankar Dey; Manas Ranjan Saha; Sumedha Roy Choudhuri; Indrani Sarkar; Biswajit Halder; Mousumi Poddar-Sarkar; Arnab Sen; Tapas Kumar Chaudhuri (Hindawi Limited, 2019)
The extracts of different parts of Nerium oleander L. are used as antidiabetic remedy in the traditional medicinal systems of different parts of the world. Despite these uses in ethnomedicinal system, the antihyperglycemic potentials of oleander stem (NOSE) and root (NORE) extracts have not been pharmacologically evaluated. Therefore, we aimed at evaluating the antidiabetic ethnomedicinal claims of NOSE and NORE, primarily focusing on glucose homeostasis and associated metabolic implications. Alloxan-treated mice with hyperglycaemia (blood glucose >200 mg/dL) were treated with oleander 70% hydromethanolic extracts (200 mg/kg) for 20 consecutive days, and the results were compared with positive control glibenclamide. Blood glucose level was 52-65% lowered (P<0.001) in oleander treated groups, which was otherwise 4.62 times higher in diabetic mice, compared to control. Insulin resistance was lowered 51-36% irrespective of any significant (P>0.05) changes in insulin sensitivity throughout the treatments. Improved serum insulin remained associated with lowered glucose level (rP = −0.847 and −0.772; P<0.01). Markers of hyperglycaemia-related hepatic glycogen, glycated haemoglobin (HbA1c), hyperlipidaemia, hepatic injury, and diabetic nephropathy were normalized as well. Improvement of systemic intrinsic antioxidant enzymes (catalase and peroxidase) were correlated (rP = −0.952 to −0.773; P<0.01) with lower lipid peroxidation by-product malondialdehyde (MDA) in the circulation. Principal component analysis coupled with hierarchical cluster analysis represented shift in metabolic homeostasis in diabetic mice, which was further normalized by oleander and glibenclamide treatment. Additionally, molecular docking studies of the phenolic acids measured by HPLC with intracellular cytoprotective transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) revealed strong molecular interactions. The results collectively support the ethnomedicine antidiabetic claims of oleander stem and root and suggest that the oleander mediated elevation of systemic antioxidant status is likely responsible for the improved glycaemic control.